Seismic geomorphological analysis of submarine fan architecture in the Baiyun Sag, Pearl River Mouth Basin: Impact of second-order relative sea-level change - Wang, Jiahao; Pang, Xiong; Wang, Hua; Zhang, Zhongtao; Liu, Baojun; La Croix, Andrew D. (Marine geology, 2024)
Whereas the effects of high-order relative sea level change (3rd-order and higher) on the formation and architecture of submarine fan systems are relatively well established, a lack of large-scale spatial and temporal data has resulted in the impacts of low-order relative sea level change (i.e., 2nd-order) eluding characterization. With the aim of revealing the impacts of 2nd-order relative sea level, this study applied regional-scale seismic geomorphology to examine 142 Miocene-aged (21–8.2 Ma) submarine fans in the Baiyun Sag of the Pearl River Mouth Basin (China), integrating a large 3D seismic volume (6000 km2), well logs and core data. By extracting seismic attributes calibrated to well data, architectural elements were interpreted, statistically correlated, and their evolution through time was assessed. The results were as follows: (1) architectural elements of submarine channels and lobes, as well as associated highstand deltas, shelf-margin deltas and incised valleys, were identified based on their seismic geomorphological features and location, revealing that submarine channels shift paleo-seaward from incised valleys and feed lobes; (2) there is a positive correlation between average width of submarine channels and average area of lobes, as well as between the average width of incised valleys and average width of submarine channels; (3) the size of architectural elements is inversely related to proportion of sand; and most importantly, (4) the size variation of architectural elements coincides with changes in 2nd-order relative sea level. Results also indicate that rapid tectonic subsidence played an important control on the size and sandiness of deep-water architectural elements. The findings of this study may inform reconstruction of submarine fan systems and prediction of their petroleum reservoir potential in other systems globally. •Submarine fan architectural elements were identified.•Two positive correlations between the architectural elements were revealed.•Second-order relative sea level had controlled the sizes and lithology of architectural elements.